Pelaksanaan Perpanjangan Uang Wajib Tahunan Otorita Sampai Dengan Perpanjangan Hak Guna Bangunan Di Kota Batam (Studi Kasus Kantor Notaris/PPAT Andreas Timothy, S.H., M.Kn.) - Lendrawati Lendrawati; Gusita Christa (Jurnal Selat, 2015)
Problems often occur in the management of UWTO extension until the extension of the HGB is long term processing time. Whereas the request for an extension not new appliacation. The method used in this research is observation, interview, literature study, design and simulation. Research resut in the office of Notary/PPAT Andreas Timothy, S.H., M.Kn is form procedures for handling UWTO extension until extension of HGB, form completeness of the maintenance file extension UWTO, form completeness of maintenance file extension HGB and monitoring programs are designed with Microsoft Office Excel. The design of the completeness of this file is designed to enable employees of the Office Notary/PPAT to understand the procedures for handling UWTO extension until extension of HGB when explaining to clients. Key words: Extension, UWTO, HGB, Form, Design, Clients.